Islam dan Piranti Manusia Modern di Era Digitalisasi : Kajian Konstruk Pendidikan Islam - Zaini, Zaini; Nisak, Siti Khoirun (State Islamic Institute of Madura, 2021)
In this piper the author tries to formulate Islamic education in overcoming the spirituality crisis of modern humans whose foundation is scientism. It is hoped that the Islamic spirit can fill the fragility of the human heart and soul to return to the path of Islamic guidance from the frenetic hedonism and hegemony of the digitalization era. The method used in this research is library research and multy stake random sampling survei, the data collection is taken from books, magazines, newspapers, articles and so on, then analyzed using data analysis techniques. The research results describe; portrait of modern humans in the era of digitalization in the view of Islam, the tools needed by modern humans in the era of digitalization and the construction of Islamic education in the era of digitalization. The results of this research are none other than one of the offers to manage all the potential possessed by every human person in the process of self-actualization in the era of digitalization and building relevant and humane Islamic education constructs.